Effect of emancipative values on life satisfaction across different levels of democracy: A cross-national analysis of the World Values Survey - Guillaume Barbalat; Nicolas Franck (PLoS ONE, 2025)
Emancipative values – advocating for personal freedoms, equality, and autonomy – are theorized to enhance life satisfaction by fostering empowerment and opportunities. The current study tested whether their impact is context-dependent, influenced by societal norms and institutional frameworks. We used data from wave seven of the World Values Survey (WVS) and the Varieties of Democracy (V-Dem) dataset, covering diverse countries and time periods. We examined the interaction between emancipative values and a country’s level of liberal democracy on life satisfaction using a random effects model accounting for country-level variations (random intercept and slope). The model was adjusted for individual-level variables, such as settlement size, income, and educational attainment, as well as country-level factors like lagged income per capita and regional affiliation. This approach allowed us to investigate the direct effect of emancipative values across different democratic contexts. Our final dataset included N = 76,702 participants across 58 countries. Countries with the highest levels of liberal democracy were also the most economically prosperous. Individuals in democratic nations were older, resided predominantly in larger settlements, demonstrated the highest levels of educational attainment, reported the highest incomes, and expressed the strongest adherence to emancipative values. Our random effect model revealed a negative main effect of emancipative values on life satisfaction. A significant positive interaction between democracy and emancipative values was also identified. Less democratic countries demonstrated a negative effect of emancipative values while no significant effect was observed in more democratic contexts. Overall, our study challenges the notion that emancipative values universally enhance life satisfaction, highlighting the significance of cultural and institutional congruence in assessing how personal values affect well-being. These findings emphasize the importance of considering contextual factors when examining the relationship between individual values and life satisfaction across diverse political and cultural landscapes.